2016
DOI: 10.3906/sag-1508-114
|View full text |Cite
|
Sign up to set email alerts
|

Cryptogenic organizing pneumonia: clinical and radiological features, treatment outcomes of 17 patients, and review of the literature

Abstract: Background/aim: We evaluated patients with cryptogenic organizing pneumonia (COP) who attended our clinic. Materials and methods:We retrospectively investigated the clinical and radiological findings, diagnostic methods, treatment, and follow-up outcomes of 17 patients who had been histopathologically diagnosed with COP. Results:The mean age of the patients was 49.8 ± 10.4 years. The most common symptom was cough (n = 15; 88.2%) and the most common radiological finding (n = 10) was consolidation in the inferio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
3
10
1
Order By: Relevance
“…In our study, the mean age of onset was 58 years, and patients were aged between 25 and 84 years; a predominance in women (68%) was observed. These data are in line with the study of Niksarlioglu et al [38] and the study of Lee et al [39]. COP is usually a no smoke-related disease; our results confirm this data, as seen also in Niksarlioglu's and Lee's studies, with only five patients currently or ex-smokers (80.8% non-smokers).…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In our study, the mean age of onset was 58 years, and patients were aged between 25 and 84 years; a predominance in women (68%) was observed. These data are in line with the study of Niksarlioglu et al [38] and the study of Lee et al [39]. COP is usually a no smoke-related disease; our results confirm this data, as seen also in Niksarlioglu's and Lee's studies, with only five patients currently or ex-smokers (80.8% non-smokers).…”
Section: Discussionsupporting
confidence: 94%
“…These results are in line with previous papers published by Faria et al (who reported typical pattern in 83% patients) [41] and by Lee et al (who reported typical pattern in 77% patients) [39]. The second most prevalent radiological pattern was represented by GGOs; in our study, we observed GGOs in 68.1% of patients, unlike what has been reported in previous studies about this subject, where patients have shown GGOs in a range between 86% and 89% [36,38]. The atoll sign was found in four patients (18.1%), similar to the description of Kim et al in their study of 2003 [29].…”
Section: Radiological Findingsupporting
confidence: 93%
See 3 more Smart Citations